2010
DOI: 10.1007/s00294-010-0298-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a CuZn superoxide dismutase gene in the arbuscular mycorrhizal fungus Glomus intraradices

Abstract: To gain further insights into the mechanisms of redox homeostasis in arbuscular mycorrhizal fungi, we characterized a Glomus intraradices gene (GintSOD1) showing high similarity to previously described genes encoding CuZn superoxide dismutases (SODs). The GintSOD1 gene consists of an open reading frame of 471 bp, predicted to encode a protein of 157 amino acids with an estimated molecular mass of 16.3 kDa. Functional complementation assays in a CuZnSOD-defective yeast mutant showed that GintSOD1 protects the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 65 publications
2
26
0
Order By: Relevance
“…This is the order of pollution increase, too, similar results also being published by González-Guerrero et al [53] and, Neagoe et al [13,14]. What is interesting, in contrast with very contaminated substrates such as mine tailings [12][13][14], is that the response of oxidative stress variables for plants grown in unpolluted or slightly polluted soils presents similar patterns of variation in almost all plant parts.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…This is the order of pollution increase, too, similar results also being published by González-Guerrero et al [53] and, Neagoe et al [13,14]. What is interesting, in contrast with very contaminated substrates such as mine tailings [12][13][14], is that the response of oxidative stress variables for plants grown in unpolluted or slightly polluted soils presents similar patterns of variation in almost all plant parts.…”
Section: Resultssupporting
confidence: 66%
“…In conclusion, the excess of metals involves the induction of lipid peroxidation in plants, which causes the degradation of lipoprotein membrane by lipid peroxidation, which could also include the degradation of photosynthetic pigments, causing deterioration in growth [52]. The presence of stress-tolerant mycorrhyzal fungi could reduce MDA content according to González-Guerrero et al [53] and Abdel Latef [48]. Positive effects of natural inoculation can be seen in protein content, which is huge in comparison with all other treatments.…”
Section: Resultsmentioning
confidence: 99%
“…This gives evidence on the involvement of fungal reactive oxygen species-scavenging systems in plant-fungi interactions. Further studies have suggested that reactive oxygen species and SOD produced from Oidiodendron maius and Glomus intraradices play a pivotal role in mycorrhizal symbiosis (Abba et al 2009 ;Gonzalez-Guerrero et al 2010 ). A necrotrophic fungus, Sclerotinia sclerotiorum , was found to repress defensive mechanisms of host plants such as Lycopersicon esculentum , Nicotiana benthamiana , or N. tabacum (Veluchamy et al 2012 ).…”
Section: Root Exudates and Plant-mycorrhizal Interactionsmentioning
confidence: 98%
“…Baseline range and threshold cycle (Ct) values were automatically calculated using iCycler software. Transcript levels were normalized to the Ct value of GintEF1α (Gonzàlez-Guerrero et al 2010) for the fungal gene and MtTef (Hohnjec et al 2005) for plant gene. Only Ct values leading to a Ct mean with a standard deviation below 0.5 were considered.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%